Dosimetry and Quality Assurance in Radiotherapy - Manihel, Salwan Hassan; Ghali, Zakaria Raad; Hamid, Sara abdul Aalee; Marid, Hamid Tuama; Mustafa, Um albanen Hiyder (American Journal of Botany and Bioengineering, 2025)
Product quality is loosely defined as all the attributes and features of a product that influence its ability to meet the needs of the consumer. The term quality assurance or QA encompasses all of the practices, systems and criteria that ensure a product consistently meets the necessary quality requirements. In radiotherapy, the product being delivered is the intended dose to the patient. The assurance of this quality is typically achieved by the accurate, precise and reproducible execution of . The process of radiotherapy involves a series of complex processes and steps, including the architectural setting of the beam, the calibration of the treatment device, Imaging for the purpose of verification and localization, treatment planning, and finally the delivery of treatment. Each of the above-mentioned processes has the potential to introduce error and deviation in patient dose delivery. In order to ensure that patient safety is paramount and that the prescribed offering is delivered both accurately and accurately, good-quality quality assurance (QA) practices are needed. Furthermore, record and review the acceptability of each treatment field before the patient is treated. It is a guide before and during treatment to determine how well the planned therapy session will be accurately and accurately administered. Two arms of this standard are the measurement of portal doses and the reconstruction of calculated doses (verifiable from portals). In this study, methods of dos variance detection of off-line portal doses were evaluated. In addition, the results of experiments investigating the portal dose were reported and compared with the results of such experiments in the literature; many of which are focused on planar dosimetric software analysis rather than the analysis of portal pixel values directly. Finally, the importance of seeds is lower and the seeds are high in beam orientations and the noise in the seed distribution is lower.